Revision of the Madagascan genera Oncodopus Brongniart and Colossopus Saussure (Orthoptera: Tettigoniidae: Conocephalinae; Euconchophorini), with description of Malagasopus gen. nov. - Ünal, Mustafa; Beccaloni, George W. (Zootaxa, 2017)
The endemic Madagascan genera Oncodopus Brongniart and Colossopus Saussure are revised using museum specimens, including the types, and recently collected material. A new genus, Malagasopus gen. nov., and seven new species, Malagasopus desutterae sp. nov., Malagasopus meridianus sp. nov., Oncodopus janetae sp. nov., Oncodopus brongniarti sp. nov., Oncodopus saussurei sp. nov., Oncodopus soalalaensis sp. nov. and Colossopus parvicavus sp. nov. are described. Lectotypes are designated for Oncodopus zonatus Brongniart, 1897 and Colossopus redtenbacheri (Brongniart, 1897). A new term, mesothoracic auricle, is proposed for a structure on the episternum of the mesothorax. A tabulated key to the genera and keys to the species are presented. All species are described and diagnosed, and their phylogenetic relationships, geographical distributions, habitat preferences and phenologies are documented. The life history of Colossopus grandidieri is described, and the unusual possible mate-guarding behaviour of several species is discussed. Maps showing the distribution of the species are presented, as too are 57 photographs of museum specimens, 51 drawings of morphological characters, 17 photographs of living specimens and one habitat photograph.